'Creative Ferment': abortion and reproductive agency in Bessie Head's Personal Choices trilogy. Issue 3 (23rd April 2021) - Stobie, Caitlin E
Abstract : Using original archival research from Amazwi South African Museum of Literature, this article examines representations of abortion in three novels by Bessie Head: When Rain Clouds Gather (1968), Maru (1971) and A Question of Power (1973). I argue that Bessie Head documents both changing attitudes to terminations of pregnancy and dramatic environmental, medical, and sociopolitical developments during southern Africa's liberation struggles. Furthermore, her fictional writing queers materialism and its traditionally gender-dichotomous origins, presenting an understanding of development which exceeds temporal or national boundaries. Her treatment of human reproduction in both tangible and figurative terms disrupts teleological definitions of exile: separation and loss, rendered through literal and metaphorical abortions, are seen as inherently vital processes for gaining agency in post/colonial southern Africa. Instead of using discourse from contemporary debates about freedom and choice, which are often polarised, I use the term 'reproductive agency' to refer to a continuum of ethical presentness, rooted in considering women's desires. My literary analysis explicitly concentrates on Head's biological imagery of growth and separation and how this ruptures repronormative discourse underpinning colonial expansion in southern Africa. I refer to Head's ethical outlook as a critical form of humanism. My understanding of critical humanism differs from humanism proper in that it relies on queer associations: both queerness as strangeness, and queerness as resistance to categorisation (much like Head's critiques of essentialist national identities). Adapting new materialist theories with postcolonial scholarship, I coin the term 'queer vitality' to argue that abortion involves both tragedy and desire, and that southern African feminist fiction functions as postcolonial theory when the concept of reproductive agency is understood to encompass both individual and collective desires. In Head's words, in her creative worlds, abortion does not signal the ending of a life, but rather a plethora of new possibilities.